Moderate or severe low back pain is associated with body mass index amongst community-dwelling older Australians - Gilmartin-Thomas, Julia FM; Cicuttini, Flavia M; Owen, Alice J; Wolfe, Rory; Ernst, Michael E.; Nelson, Mark R; Lockery, Jessica; Woods, Robyn L; Britt, Carlene; Liew, Danny; Murray, Anne; Workman, Barbara; et al. (Archives of gerontology and geriatrics, 2020)
•Approximately one in six community-dwelling Australians aged 70 years or older report moderate or severe low back pain experienced on most days.•About half of those reporting moderate or severe low back pain take regular analgesic medication, approximately one-third report regular interference with sleep or walking, and almost half report regular interference with day to day activities.•Moderate or severe low back pain is associated with either an overweight or obese body mass index among community-dwelling older Australians. Low back pain is prevalent in older populations and modifiable risk factors may include being overweight or obese. This study aimed to describe the prevalence and impact of moderate or severe low back pain in community-dwelling older adults and its association with body mass index (BMI). Cross-sectional study involving 16,439 Australians aged ≥70 years. Logistic regression was used to describe associations between the presence or absence of moderate or severe low back pain experienced on most days with BMI. Analyses were conducted separately for males and females, and controlled for age and depression at baseline. Of 14,155 pain question respondents, 11 % of males (n = 710/6475) and 18 % of females (n = 1391/7680) reported moderate or severe low back pain (total 15 %, n = 2101/14,155). Of those reporting moderate or severe low back pain (n = 2101), 55 % reported taking pain-relieving medication regularly, and 29 % reported that the pain regularly interfered with sleep, 37 % with walking, and 47 % with day to day activities. When age and depression were controlled for, there was a statistically significant (p < 0.001) association between moderate or severe low back pain and being overweight (females: odds ratio OR = 1.50, 95 % confidence interval CI = 1.27−1.76) or obese (males: OR = 2.23, 95 %CI = 1.77−2.80 and females: OR = 2.91, 95 %CI = 2.48−3.42). Moderate or severe low back pain is common, has a significant impact, and is associated with either an overweight or obese BMI among community-dwelling Australians aged ≥70 years.